DESIGN OF SUBSONIC WIND TUNNEL AND DETERMINATION OF AERODYNAMIC COEFFICIENT - RAHMAN, MD RAFIQUR (IJRDO - Journal of Mechanical And Civil Engineering, 2021)
Open circuit subsonic wind tunnel is an experimental set up which is widely used in the field of Aerodynamic research. With the help of wind tunnel we can determine Aerodynamic coefficient of any solid object which is moving through air. This paper deals with a study of small scale open circuit wind tunnel design and test. In this paper low velocity wind tunnel was designed and fabricated to reduce the drag and lift forces. A typical open circuit wind tunnel consists of motor, fan unit, settling chamber, honey comb, contraction cone, diffuser and a test section. The main work of a wind tunnel is to improve the design according the aerodynamic shapes. It is vital to obtains reliable aerodynamic characteristics estimation to carry out a good design of any solid moving object. In this paper with the help of wind tunnel we will determine the aerodynamic coefficient of different types of projectiles used in military. Here a set of hollow projectile is considered to study aerodynamic characteristics of projectile in an open circuit subsonic wind tunnel where uniform flow velocity is maintained across the flow direction. Here we have used the inclined manometer to find out surface static pressure and then the pressure coefficient was determined.